ANALYSIS OF MARKETING STRATEGIES IN INCREASING THE NUMBER OF STUDENTS OF MARKAZ TAHFIZH TODDLERS AND CHILDREN (MATABA) DAARUL HUFFAZH IN THE CITY SERANG BANTEN - Umi Nurasih; Syarif Hidayatullah; Moh. Tahang (Journal Of Applied Multidisiplinary Studies, 2024)
Competition between tahfizh schools in Indonesia is getting tighter, especially with the emergence of various tahfizh institutions for toddlers and children. This study aims to analyze the marketing strategy used by Markaz Tahfizh Toddlers and Children (MATABA) Daarul Huffazh in Serang Banten in increasing the number of students. The purpose of this research is to analyze MATABA's marketing strategy, how segmentation and positioning are carried out, as well as the obstacles faced in the marketing process. The research uses a descriptive qualitative approach with case studies. Data collection was carried out through observation, interviews, and document review. The results of the research by analyzing the ongoing marketing strategy, namely direct and indirect marketing strategies, STP and 7P marketing mix show that MATABA's marketing strategy is unique through the Tabarak and Tahsin Tilawati tahfidz methods with learning program innovations designed by the curriculum team which is a differentiation so that it has its own attractiveness, even though there is no special marketing team that is an obstacle in expanding Promotional reach. Customers are generally satisfied with the services and programs offered by MATABA, but a more structured marketing strategy is needed to increase the number of students on a sustainable basis.